2016
DOI: 10.3802/jgo.2016.27.e56
|View full text |Cite
|
Sign up to set email alerts
|

Can human papillomavirus (HPV) genotyping classify non-16/18 high-risk HPV infection by risk stratification?

Abstract: ObjectiveInfection with high-risk genotypes of human papillomavirus (HR-HPV) is the major cause of invasive cervical cancers. HPV-16 and HPV-18 are known to be responsible for two-thirds of all invasive cervical carcinomas, followed by HPV-45, -31, and -33. Current guidelines only differentiate HPV-16/18 (+) by recommending direct colposcopy for treatment. We tried to evaluate whether there are differences in risk among 12 non-16/18 HR-HPV genotypes in this study.MethodsThe pathology archive database records o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 22 publications
0
7
0
4
Order By: Relevance
“…A 5‐year study by Uijterwaal et al found that non‐HPV 16/18‐positive women with normal cytology also had an 11.4% HSIL risk. Sung et al also found that some of the 12 non‐HPV16/18 genotypes has are associated with the same risk of HSIL as HPV16/18. Thus, the patients with non‐HPV16/18 infection should be referred to colposcopy.…”
Section: Discussionmentioning
confidence: 96%
“…A 5‐year study by Uijterwaal et al found that non‐HPV 16/18‐positive women with normal cytology also had an 11.4% HSIL risk. Sung et al also found that some of the 12 non‐HPV16/18 genotypes has are associated with the same risk of HSIL as HPV16/18. Thus, the patients with non‐HPV16/18 infection should be referred to colposcopy.…”
Section: Discussionmentioning
confidence: 96%
“…According to HPV 9G DNA chip results, the odds ratios for worse than or equal to high grade squamous intraepithelial lesions (≥HSIL) of patients infected with HPV 16/18, HPV 31/33/35/45/52/58, and HPV 39/51/56/59/66/68, compared with HR HPV negative, were 18.1, 11.9, and 2.4, respectively. 18 …”
Section: Discussionmentioning
confidence: 99%
“…Os genotipos são divididos em "tipo de alto risco", onde se encaixam os conhecidos como oncogênicos (genotipos 16, 18, 31,33, 35, 39, 45, 51, 52, 58 entre outros), e em "tipo de baixo risco" que geralmente causam lesões benignas, como os genotipos 6,11,40,42,43,44 (Cordel et. al., 2015;Sung et. al., 2016;.…”
Section: Lista De Figurasunclassified
“…Os Papilomavírus Humano são vírus capazes de infectar a pele ou as mucosas. Atualmente, são conhecidos mais de 150 tipos de HPV e cerca de 40 destes possuem afinidade pelo epitélio escamoso do trato genital inferior, que é composto pelo colo, vulva, corpo do períneo, região perianal e anal (INCA, 2016;Sung et al, 2016).…”
Section: Infecção Por Papilomavírus Humanounclassified
See 1 more Smart Citation